ChIP‐seq and transcriptome analysis of the OmpR regulon of Salmonella enterica serovars Typhi and Typhimurium reveals accessory genes implicated in host colonization. Issue 3 (19th December 2012) - Perkins, Timothy T.; Davies, Mark R.; Klemm, Elizabeth J.; Rowley, Gary; Wileman, Thomas; James, Keith; Keane, Thomas; Maskell, Duncan; Hinton, Jay C. D.; Dougan, Gordon; Kingsley, Robert A.
Summary OmpR is a multifunctional DNA binding regulator with orthologues in many enteric bacteria that exhibits classical regulator activity as well as nucleoid‐associated protein‐like characteristics. In the enteric pathogen Salmonella enterica, using chromatin immunoprecipitation of OmpR:FLAG and nucleotide sequencing, 43 putative OmpR binding sites were identified in S. enterica serovar Typhi, 22 of which were associated with OmpR‐regulated genes. Mutation of a sequence motif (TGTWACAW) that was associated with the putative OmpR binding sites abrogated binding of OmpR:6×His to the tviA upstream region. A core set of 31 orthologous genes were found to exhibit OmpR‐dependent expression in both S. Typhi and S. Typhimurium. S. Typhimurium‐encoded orthologues of two divergently transcribed OmpR‐regulated operons (SL1068–71 and SL1066–67) had a putative OmpR binding site in the inter‐operon region in S. Typhi, and were characterized using in vitro and in vivo assays. These operons are widely distributed within S. enterica but absent from the closely related Escherichia coli. SL1066 and SL1067 were required for growth on N‐acetylmuramic acid as a sole carbon source. SL1068–71 exhibited sequence similarity to sialic acid uptake systems and contributed to colonization of the ileum and caecum in the streptomycin‐pretreated mouse model of colitis.